DIGITAL AND INFLUENCER MARKETING: THE ROLE OF PURCHASE INTENTION IN PURCHASE DECISIONS - Rahmad Dianta Purba; Noniya Dewinta Anggi Ritonga (Jurnal Terapan Ilmu Manajemen dan Bisnis, 2026)
This study aims to analyze the effect of digital marketing and influencer marketing on purchase decisions, with purchase intention as a mediating variable in Bolu Menara MSMEs. The research method used is a quantitative approach with data collection through questionnaires administered to consumers, and data analysis using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results show that digital marketing and influencer marketing have a positive and significant effect on purchase intention and purchase decisions, both directly and indirectly. In addition, purchase intention is proven to significantly mediate the effect of digital marketing and influencer marketing on purchase decisions. The research model has strong coefficients of determination (R²) and predictive relevance (Q²), indicating that the model has good explanatory and predictive power. These findings indicate that the effectiveness of digital marketing strategies and the use of influencers should focus on increasing consumer purchase intention to drive purchase decisions.